Фольклорная палитра кинематографического наследия Сергея Параджанова - Nikoriak, Nataliia (My University, 2021)
Folklore, as an inexhaustible source of inspiration for artists of different eras, has become an important part of the creative heritage of director and screenwriter Sergey Parajanov, who managed to present Ukrainian, Armenian, Georgian and Azerbaijani cinematographic samples to the whole world. The director’s interest in “folklore motives” was already apparent in his diploma project – a screen adaptation of a Moldavian verse fairy tale “Andriesh” (1951). However, a powerful “explosion” of authenticity occurred much later, in the film “Shadows of Forgotten Ancestors” (1964), in the movie parable “Sayat Nova” (“The Color of Pomegranates”, 1969), in “The Legend of Suram Fortress” (1984) and in the movie tale “Ashik-Kerib”(1988). There were also two incomplete attempts to read folklore texts, for example, “Ara the Beautiful”, which was based on the ancient Armenian legend about Ara the Beautiful and Semiramis and the philosophical tale “The Miracle in Odense” (about Hans Christian Andersen). It is significant that the “appeal to folklore” became one of the key features in S. Parajanov’s subsequent style.
Folklore Variety of Sergei Parajanov’s Cinematographic Works
Keywords: Folklore; Sergey Parajanov; “Shadows of Forgotten Ancestors”; “The Color of Pomegranates”; “The Legend of Suram Fortress”; “Ashik-Kerib”